The Quotable Saint Jerome - Jerome, Saint, -419 or 420 (Book collections on Project MUSE., 2020)
"To honor the 1600th anniversary of the death of this patron saint of librarians and Scripture scholars, The Catholic University of America Press is releasing The Quotable Saint Jerome, a well-organized collection of memorable wisdom from this early witness to Catholic truth. It features short selections of what Jerome said on any number of topics-Scripture, the Trinity, the sacraments, persecution, heresy, divine revelation, or chastity-just to name a few. All citations are clearly sourced if the reader wants to pursue the longer passage in question. Contains a list of works cited and an index"--